2015
DOI: 10.1021/acs.jafc.5b04400
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Antihyperlipidemic Properties of a Triterpenoid Compound, Dehydroeburicoic Acid, from Antrodia camphorata in Vitro and in Streptozotocin-Induced Mice

Abstract: The aim of this study was to examine the effects of dehydroeburicoic acid (TT) on type 1 diabetes mellitus and dyslipidemia in streptozotocin (STZ)-induced diabetic mice. STZ-induced diabetic mice were randomly divided into six groups and given orally by gavage TT (at three dosages), metformin (Metf), fenfibrate (Feno), or vehicle for 4 weeks. STZ-induced diabetic mice showed elevations in blood glucose levels (P < 0.001). TT treatment markedly decreased blood glucose levels by 42.6-46.5%. Moreover, STZ-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 55 publications
(117 reference statements)
4
63
0
Order By: Relevance
“…It is no surprise that our results are similar to previous studies [17,[28][29][30][31] showing that both CO and TC efficiently controlled impaired glucose metabolism and improved hyperglycemia. However, our results are inconsistent with previous studies in that TC did not inhibit weight gain or reduce lipid accumulation [28][29][30]. This might be due to the longer-term high-fat diet induction experiment (HFD for 24 weeks) in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is no surprise that our results are similar to previous studies [17,[28][29][30][31] showing that both CO and TC efficiently controlled impaired glucose metabolism and improved hyperglycemia. However, our results are inconsistent with previous studies in that TC did not inhibit weight gain or reduce lipid accumulation [28][29][30]. This might be due to the longer-term high-fat diet induction experiment (HFD for 24 weeks) in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that TC can reduce obesity and attenuate hyperglycemia in rodents, and may act by regulating the composition of the gut microbiota [28][29][30]. It has also been confirmed that CO inhibits hyperlipidemia and hyperglycemia [17,31].…”
Section: Discussionmentioning
confidence: 82%
“…A group of control (CON) mice ( n = 7) were gavaged identical volumes of vehicle. The STZ mice that were found to develop hyperglycemia, defined as fasting blood glucose above 250 mg/dL, were considered to have diabetes for this study [25]. The STZ-induced diabetic mice ( n = 48) were then randomly divided into six groups.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting pellet was resuspended in a small amount of buffer (about 0.5 mL) as a total membrane fraction [27,28]. The expression levels of GLUT4, phospho-AMPK, and total AMPK were determined by Western blotting as previously described [25,26]. …”
Section: Methodsmentioning
confidence: 99%
“…It exhibits antitumor activity against the human glioblastoma U87MG [2] [5]. It has an excellent therapeutic potential for the treatment of type 1 diabetes and type 2 diabetes [6] [7]. Human serum albumin (HSA) is significant in the blood circulatory system.…”
Section: Introductionmentioning
confidence: 99%